Investigating the Influencing Aspects of User Continuance Intention of Google Workspace Ecosystem in Academic Environment based on Extended Expectation Confirmation Model (E-ECM) - Nabil, Faiqi; Devi Ajeng Efrilianda (Universitas Negeri Semarang, 2025)
The application of cloud software-as-a-service (SaaS) services is widely adopted to help various activities and work, including academic activities. One of the SaaS services is the Google Workspace ecosystem, which significantly transforms academic institutions and students in managing information, collaborating, and maximizing productivity. However, some users still switch back to conventional software, and there is intense market competition from similar companies. In addition, acquiring new users costs five times more than keeping existing users. Thus, this study aims to investigate the reasons or aspects that influence users to continue adopting the Google Workspace ecosystem in the academic environment. To achieve this goal, this study adopts the extended expectation confirmation model (E-ECM). This study uses a quantitative method with a purposive sampling technique to determine the sample respondents, namely active undergraduate students of Universitas Negeri Semarang who use the Google Workspace ecosystem for academic purposes. A total of 390 valid data were obtained from distributing questionnaires online. The analysis identified that satisfaction, trust, and perceived usefulness directly influence user continuance intention. Then, satisfaction is directly influenced by confirmation, institutional support, and service quality. Then, trust is directly influenced by satisfaction, system quality, and service quality. In addition, perceived usefulness is also directly influenced by confirmation. The results of this study are expected to be taken into consideration by stakeholders and future researchers.